Analisis Strategi Pemasaran Bukit Muncak Temiangan Kabupaten Lampung Barat - Manullang, Bryan Nielsen; Barusman, Tina Miniawati (Jurnal EMT KITA, 2024)
This research aims to conduct a marketing strategy analysis at the Muncak Temiangan Hill tourist attraction in West Lampung Regency. This research was conducted with the guidance of Dr. Tina Miniawati Barusman, SE., M.BA. Muncak Temiangan Hill is a tourist destination that combines the beauty of natural panoramas with various aspects of tourism to create significant economic value. However, based on observations of these tourist attractions, there was a 90% decrease in the number of visitors in 2021 compared to the previous year. By identifying these problems, the main aim of this research is to conduct a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis on Muncak Temiangan Hill Tourism. The research method used is a narrative approach with a qualitative approach. Data was collected through interviews, observation, and documentation. SWOT analysis and SWOT matrix are used to formulate and select optimal marketing tactics to increase the attractiveness of Muncak Temiangan Hill and overcome the decline in the number of visitors.